Effect of Zinc Chloride on the Sludge Carbon-Based Adsorbent in Diesel Desulfurization. Issue 3 (February 2020) - Jin, Mei; Hu, Bao; Tang, Xinnan; Zou, Linling; Yu, Guoxian
Abstract: Sulfur compounds in diesel oil can be removed by adsorption technology. Based on urban sludge as the main raw materials, activated sludge carbon-based absorbent was prepared through the cothermalization of urban sludge and rice hull by adding ZnCl2 as the chemical activator. The obtained absorbent was characterized by nitrogen adsorption, elemental analysis, FT-IR characterization. The textural structure and pore distribution results showed that the amount of the micropore and the surface area played the important roles on the adsorption capacity. The elemental analysis results revealed that the percentage of C element was the key factor in the adsorption experimental. FT-IR characterization results illustrated that the oxygen-containing groups on the absorbent surface increased significantly with the addition of ZnCl2 activator, especially the amount of alcohol hydroxyl groups and quinone hydroxyl groups. ZnCl2 activated sludge carbon-based adsorbent was applied in the adsorption capacity of dibenzothiophene with model oil. As a result, the adsorption capacity was up to 19.9 mg S/g at ZnCl2 concentration of 50 wt %, which can provided a new way for harmless and resource recovery of urban sludge.